THE EAST AFRICAN COMMUNITY ELECTRONIC LIBRARY: DOCUMENTING THE REGIONAL INTEGRATION PROCESS - Kagoda-Batuwa, Sarah (My University, 2012)
The East African Community (EAC) is a regional intergovernmental organisation with a membership of five countries. Since its establishment in 1999 the Community has generated a lot of information and knowledge through its various integration processes of a Customs Union, Common Market and Monetary Union. The Community has therefore embarked on the process of digitizing its information resources and knowledge and making these available online. The existing library will be transformed into an electronic information resource centre that will act as a central access point for EAC information and knowledge. The digitization project is a collaborative effort of the various organs and institutions of the Community, aimed at documenting the East African regional integration process for preservation and prosperity. The project will benefit the various stakeholders, including partner states, students and researchers. The paper will discuss the planned digitization process, methodology and anticipated challenges.
Keywords: THE EAST AFRICAN COMMUNITY ELECTRONIC LIBRARY: DOCUMENTING THE REGIONAL INTEGRATION PROCESS